EFEK MODEL PEMBELAJARAN PROBLEM SOLVING DAN MOTIVASI TERHADAP HASIL BELAJAR FISIKA SISWA SMA - Grace Dennys Hutabarat; Sahyar , (Jurnal Pendidikan Fisika, 2013)
The Objectives of this research are (1) find out the difference oflearning outcomes Physic by Problem solving and Expository (2) differenceof students the learning outcomes with high learning motivation comparedlow learning motivation, (3) interaction between motivation and learningoutcomes of Problem solving and Expository. This study is a quasiexperimentresearchwith2x2factorialdesigns.Thepopulationin this studyis 320 students from eight classes of grade X at SMA N 1 Sidamanik, NorthSumatra. The samples of this research were two classes, consisted of 75students determined by random cluster sampling. Data were analyzed usingtwo ways ANAVA at significant level of 0.05. Research shows that (1)students learning outcomes of problem solving class is better then expositoryclass. (2) students learning outcomes with high learning motivation is better then low learning motivation (3) interaction of motivation and learningoutcomes is available in the problem solving and expository.